MAIN INDICATORS OF SOCIAL INFRASTRUCTURE DEVELOPMENT IN SMALL TERRITORIES - Qurbonov, Shuxrat Bekmetovich; Daljanov, Kazakbay Ongarbaevich (SCIENCE and SOCIETY, 2026)
This article analyzes the development indicators of social infrastructure in small areas of the Republic of Uzbekistan (rural areas and cities). The focus is on education, healthcare, and public services indicators, as well as their dynamics.
Keywords: population; service sector; paid services; retail trade; education system; healthcare; medical care; consumer services; territorial organization; transport services; social sphere